1999
DOI: 10.1007/s002689900567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retinoblastoma and Ki‐67 Immunostaining as Diagnostic Markers of Benign and Malignant Parathyroid Disease

Abstract: Assessment of the malignant potential of parathyroid tumors in the absence of metastases can be difficult using morphologic criteria alone. In this study we have examined a total of 58 parathyroid tumors (31 benign, 15 malignant, and 12 equivocal) from 54 patients using immunohistochemistry with monoclonal antibodies directed against the retinoblastoma (RB) protein and the cell cycle-associated antigen Ki-67 to evaluate their role as diagnostic markers. RB protein immunoreactivity was not useful for distinguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
4
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 25 publications
0
45
4
5
Order By: Relevance
“…Levin (40) distinguished between "typical" and "atypical adenomas." Others have chosen to label this group as "equivocal carcinomas" (22,28). We prefer the terminology "equivocal carcinoma" in the research and clinical setting, as gold-standard pathologic criteria does not accommodate a localized parathyroid carcinoma (2,27,40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Levin (40) distinguished between "typical" and "atypical adenomas." Others have chosen to label this group as "equivocal carcinomas" (22,28). We prefer the terminology "equivocal carcinoma" in the research and clinical setting, as gold-standard pathologic criteria does not accommodate a localized parathyroid carcinoma (2,27,40).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of pRb immunostaining have also yielded conflicting results. Some studies have reported that it may be a helpful marker (25,26), but several other studies have contradicted these findings (22,23). A recent review of RB gene abnormalities in parathyroid carcinoma concluded that no definitive conclusion could be drawn with regards to pRb staining (26).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the abnormality of p53 gene expression was found to vary (0-100%) in carcinomas (10)(11)(12)16,27). In addition to the p53 abnormality, the loss of Rb (11,14) and p21 (16) expression, and the accumulation of cyclin D1 (16) and p27 (28) expression suggest a disintegration of the cell cycle control, although this was not always present (up to 55%). The accelerated cell proliferation in carcinoma was successfully evaluated by displaying the increase in PCNA- (15) or the Ki-67-positive cell population.…”
Section: Discussionmentioning
confidence: 97%
“…However, a consensus has yet to be reached in identifying parathyroid carcinoma from adenoma using these markers. Only Ki-67 demonstrated a universally accepted clinical significance (10)(11)(12)(13)(14). However, several falsepositive and false-negative results in diagnosis have been reported (10,11,15,16).…”
Section: Introductionmentioning
confidence: 99%